The approach of in-situ doping ion conductor fabricated with the cathodic arc plasma for all-solid-state electrochromic devices - Min-Chuan Wang; Yu-Chen Li; Jen-Yuan Wang; Yi-Shiou Chen; Chi-Hung Su; Tien-Hsiang Hsueh; Sheng-Chuan Hsu; Jin-Yu Wu; Der-Jun Jan (AIP Advances, 2018)
The all-solid-state electrochromic device (ECD) with the one substrate structure fabricated by the reactive dc magnetron sputtering (DCMS) and in-situ doping cathodic vacuum arc plasma (CVAP) technology has been developed. The electrochromic (EC) layer and ion conductor layer were deposited by reactive DCMS and CVAP technology, respectively. The in-situ doping ion conductor Ta2O5 deposited by the CVAP technology has provided the better material structure for ion transportation and showed about 2 times ion conductivity than the external doping process. The all-solid-state ECD with the in-situ doping CVAP ion conductor layer has demonstrated a maximum transmittance variation (ΔT) of 71% at 550 nm, and a faster switching speed. The lower production cost and higher process stability could be achieved by the application of in-situ doping CVAP technology without breaking the vacuum process. Furthermore, the ion doping process with the reuse of energy during the CVAP process is not only decreasing the process steps, but also reducing the process energy consumption.